Study for the validation of evaluation indicators of electronic health records in immunization: Delphi technique - Cleide Henriqueta Praxedes Fernandes; Maria Aparecida Araújo Figueiredo (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To develop and validate indicators for the evaluation of computerized systems in vaccination rooms. Methods: Methodological study. From the construction of a logical model for managing information produced in computerized systems in vaccination rooms, an evaluation indicator matrix was developed, and its contents were validated by specialists using the Delphi method. The degree of relevance and clarity were judged, using the following parameters: agreement percentage ≥ 90%; content validity index > 0.78. Internal consistency was tested using Cronbach's alpha coefficient of 0.93. Results: Of the 55 proposed indicators, 48 were validated and composed the final matrix, with 13 in the structure dimension, 29 in the process dimension, and six in the outcome dimension. Conclusion: The set of indicators shows validity and high reliability, and can be used to evaluate computerized systems in vaccination rooms throughout the country, as it adhered to the recommendations of the National Immunization Program.